Sweden’s Rejection of Neutral / Non-Aligned Status Or Why Ukraine’s Membership in NATO Should Have No Alternative - Ігор Гурак; Ігор Цепенда; Сергій Дерев'янко (Історико-політичні проблеми сучасного світу)
Having proclaimed its neutral status in 1834, Sweden has long followed a special trajectory that allowed it to distance itself from participation in armed conflicts and military-political blocs. In the context of preparations to join the EU, the Swedish political discourse shifted from neutrality to the principles of ‘non-alignment’ and ‘military non-alignment’. At the beginning of the 21st century, neutrality virtually disappeared from the official documents of the kingdom. At the same time, Sweden was undergoing demilitarization, which was not hindered even by the war in Georgia in 2008. Only with the beginning of Russian aggression against Ukraine, the Swedes resorted to increasing military spending, military personnel, shifted focus from the foreign activity of the country’s armed forces to territorial defense, and also intensifying cooperation with NATO. A qualitative transformation of the official Stockholm approaches to the implementation of state policy in the field of security and defense emerged after the start of Russia’s large-scale war against Ukraine. In May 2022, contrary to the long-standing tradition of neutrality / non-alignment, official Stockholm applied for the country’s accession to NATO.